KOMPLEKS DAN KELIMPAHAN ARTHROPODA PADA PERTANAMAN JAGUNG Zea mays - Prihatin -; Tamrin Abdullah; Nurul Wirid annisaa; Jumardi; Nirma Septia Ramlan; Victoria Coo Lea (BIOMA : JURNAL BIOLOGI MAKASSAR, 2023)
Maize is one of the carbohydrate and protein-producing food crops besides rice. Along with the development of the food and feed industries, the demand for corn continues to increase. The limiting factor in increasing corn productivity is the attack of plant disrupting organisms, especially pests. This study aims to determine the abundance of arthropods in corn crops and group them based on their roles, as well as analyse the effect of cultivation practises on arthopod abundance. The research was conducted in Situ Gede Village, Bogor District, West Bogor City, West Java. The research was conducted from March to May 2019. Observations of arthropods in corn plants were conducted regularly starting from the vegetative phase, namely 3 weeks after planting (WAP), 5 WAP, and 7 WAP, until the generative phase (before corn harvest). Sampling of arthropods was done by observing them directly (In situ), using Pitfall traps, and using insect nets (Sweep net). The results showed that in the vegetative stage, the herbivorous insects found were armyworms (Spodoptera litura) and grasshoppers (Oxya sp.), while in the generative phase, corn borer (Helicoverpa armigera) and corn stem borer (Ostrinia furnicalis) dominated. In addition to pests, natural enemies, especially predators, were spiders, ants, and beetles. Based on their role, the composition of arthropods starts with the most predators (41%), herbivores (29%), parasitoids (6%), and other insects (24%). The abundance of arthropods is also determined by farmers' cultivation practices. The more diverse the commodities, the higher the arthropod abundance. Polyculture systems tend to have higher arthropod abundance than monoculture. Key words: arthropods, maize, natural enemies, predators